2020
DOI: 10.2174/1381612826666200701211422
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Polyphenols in Adipose Tissue Browning: A Narrative Review

Abstract: : Lifestyle modifications such as energy restriction and increased physical activity are highly effective in the management of obesity. However, adherence to these therapeutic approaches is poor. On the other hand, synthetic drugs used for obesity control are plagued by adverse effects. Despite these failures, adipose tissue is still an attractive therapeutic target for novel molecules, and thus, the characterisation of new and safer anti-obesity drugs is of signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 163 publications
0
4
0
Order By: Relevance
“…Obesity can be effectively suppressed by inhibiting the differentiation of adipocytes or promoting the decomposition of adipocytes. Moreover, it is also essential to activate brown adipose tissue and browning of white adipose tissue for anti-obesity treatment ( 26 28 ). Our experiment revealed that MA treatment can inhibit weight gain of KKay mice, and it may be at least partially mediated by the following three mechanisms:…”
Section: Discussionmentioning
confidence: 99%
“…Obesity can be effectively suppressed by inhibiting the differentiation of adipocytes or promoting the decomposition of adipocytes. Moreover, it is also essential to activate brown adipose tissue and browning of white adipose tissue for anti-obesity treatment ( 26 28 ). Our experiment revealed that MA treatment can inhibit weight gain of KKay mice, and it may be at least partially mediated by the following three mechanisms:…”
Section: Discussionmentioning
confidence: 99%
“…Catechins are polyphenols that have been claimed to have strong thermogenic and anti-obesogenic effects. Activation of PGC-1-dependent pathways, norepinephrine/catechol-O-methyl-transferase (NE/COMT) inhibition, and mitochondrial biogenesis activation have all been linked to catechins’ ability to influence thermogenesis [ 67 , 68 ]. By inhibiting COMT, a protein that is present in almost all tissues, catechins have been shown to stop the breakdown of catecholamines like norepinephrine.…”
Section: The Relationship Of Polyphenols In the Composition Of Propol...mentioning
confidence: 99%
“…Thanks to these activities, cells produce energy with greater efficiency, and the replacement of defective mitochondria (notoriously associated with aging diseases) promotes energy expenditure, increasing lipid oxidation and promoting thermogenesis [ 52 ]. Thermogenesis could also be promoted by inhibiting noradrenaline degradation at the BAT-synapse level, due to the fact that the COMT enzyme, which catabolizes this catecholamine, is inhibited by some polyphenols [ 53 ].…”
Section: Polyphenols and Obesitymentioning
confidence: 99%